Epigenetic Epidemiology of Cancer - Herceg, Zdenko; Ghantous, Akram; Chung, Felicia Fei Lei * (Springer Cham, 2022)
The epigenome has been proposed as a biosensor of past or cumulative exposures and could also be a disease mediator. Human cancers exhibit a wide range of epigenetic alterations characterized by progressive acquisition during tumorigenesis and potential reversibility. Epigenetic changes may occur early in cancer development, supporting the notion that disrupted epigenetic mechanisms precede and promote malignant transformation. Recent exciting advances in epigenomics that allow the analysis of the epigenome with unprecedented resolution have galvanized investigations in epigenetic epidemiology of cancer. Epigenome states are regulated by three basic mechanisms: DNA methylation, posttranslational histone modifications, and non-coding RNAs (ncRNAs). DNA methylation is the best characterized epigenetic modification, and it is the most extensively studied in epigenetic epidemiology. Whereas it has long been established that DNA methylation (and other epigenetic) changes are ubiquitous in tumour tissue, many recent studies provided evidence that cancer risk- and exposure-associated epigenetic changes can be detected in non-malignant adjacent tissues or surrogate tissues (such as peripheral blood), providing attractive targets for discovering novel biomarkers of exposure and risk stratification. In this chapter, we review evidence from retrospective and prospective studies supporting the utility of epigenetic markers as predictors of predisposition to cancer and risk stratification. We also discuss changes in the “epigenetic clock” associated with cancer susceptibility as well as the potential of identifying epigenetic markers from negative surgical margins as predictors of cancer recurrence risk.